FAKTOR PENDUKUNG DAN PENGHAMBAT INTENSI REMAJA BERHENTI MEROKOK - Lailatul ' Rahmah; Febriana ' Sabrian; Darwin ' Karim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract The aim of the research is to indentify the correlation between supporting and restricting factors to teenagers intention in smoking cessation. The method is descriptive correlation. This research involved 118 respondents that were taken by total sampling method. Measuring instrument used was questionnaires with 45 statements to the supporting and restricting factors related to teenagers intention in smoking cessation which have been tested for validity and reliability. The results show some supporting factors that have a correlation with intention to quit smoking are: self efficacy with p value 0,000 < 0,05, health reason with p value 0,001 < 0,05 and economic reason with p value 0,000 < 0,05. Therefore it can be concluded that the higher self efficacy, awereness of health, and economic reason the higher intention to smoking cessation. These three factors have strength of correlation distance from weak to medium. Restricting factor that have significant correlation with intention to quit smoking is: parental influence with p value 0,001 < 0,05 the stonger smoking behavior of parents, the lower intention of children to quit smoking with the strength of correlation is weak. Restricting factors that do not have correlation with intention to quit smoking are: friends influence with p value 0,251 > 0,05, tobacco advertisement with p value 0,718 > 0,05. It can be concluded that friends influence and tobacco advertisement does not affect of teenagers to smoking cessation and both these factors have very weak strength of correlation. Keywords: Behavior of smoking, intention, restricting factor, supporting factors, teenegers. References: 64 (2007-2014)